Environmental Literacy as a Determinant of Public Health: A Systematic Literature Review on Disease Preventio - Rusnita, Rusnita; Sulistiawaty, Sulistiawaty; Sahabuddin, Erma Suryani (Jurnal Biologi Tropis, 2025)
The burden of disease related to environmental conditions remains high in many communities, making improving environmental literacy a crucial prevention strategy. This study, conducted a Systematic Literature Review (SLR) of the Scopus database (2015–2025), aimed to identify educational interventions used to improve environmental literacy in the community, as well as factors supporting and inhibiting their effectiveness. A selection process yielded 17 articles for analysis. Results indicate that community-based interventions, including face-to-face counseling, health cadre training, community digital education, citizen participation in environmental monitoring, and culture-based education, often contribute to increased knowledge, awareness, and practice of disease prevention. The success of these interventions is influenced by community trust in information sources, self-efficacy, the availability of environmental facilities (trash cans, clean water, sanitation), and local leadership. Conversely, skepticism, the normalization of unhealthy behaviors, fatalism, limited infrastructure, and leadership conflict are key barriers. This study confirms that environmental literacy alone does not guarantee behavioral change without social and structural support. Future research recommendations include quasi-experimental research, long-term impact evaluations, and comparative studies across cultural contexts to strengthen evidence for implementation.